Thin TiO2Coatings by ALD Enhance the Cell Growth on TiO2Nanotubular and Flat Substrates - Motola, Martin; Čapek, Jan; Zazpe Mendioroz, Raúl; Bačová, Jana; Hromádko, Luděk; Brůčková, Lenka; Ng, Siow Woon; Handl, Jiří; Spotz, Zdeněk; Knotek, Petr; Baishya, Kaushik; Majtnerová, Pavlína; et al. (American Chemical Society, 2020)
The present work exploits Ti sheets and TiO2 nanotube (TNT) layers and their surface modifications for the proliferation of different cells. Ti sheets with a native oxide layer, Ti sheets with a crystalline thermal oxide layer, and two kinds of TNT layers (prepared via electrochemical anodization) with a defined inner diameter of 12 and 15 nm were used as substrates. A part of the Ti sheets and the TNT layers was additionally coated by thin TiO2 coatings using atomic layer deposition (ALD). An increase in cell growth of WI-38 fibroblasts (>50%), MG-63 osteoblasts (>30%), and SH-SY5Y neuroblasts (>30%) was observed for all materials coated by five cycles ALD compared to their uncoated counterparts. The additional ALD TiO2 coatings changed the surface composition of all materials but preserved their original structure and protected them from unwanted crystallization and shape changes. The presented approach of mild surface modification by ALD has a significant effect on the materials’ biocompatibility and is promising toward application in implant materials.

The present work exploits Ti sheets and TiO2 nanotube (TNT) layers and their surface modifications for the proliferation of different cells. Ti sheets with a native oxide layer, Ti sheets with a crystalline thermal oxide layer, and two kinds of TNT layers (prepared via electrochemical anodization) with a defined inner diameter of 12 and 15 nm were used as substrates. A part of the Ti sheets and the TNT layers was additionally coated by thin TiO2 coatings using atomic layer deposition (ALD). An increase in cell growth of WI-38 fibroblasts (>50%), MG-63 osteoblasts (>30%), and SH-SY5Y neuroblasts (>30%) was observed for all materials coated by five cycles ALD compared to their uncoated counterparts. The additional ALD TiO2 coatings changed the surface composition of all materials but preserved their original structure and protected them from unwanted crystallization and shape changes. The presented approach of mild surface modification by ALD has a significant effect on the materials’ biocompatibility and is promising toward application in implant materials.
Thin TiO2Coatings by ALD Enhance the Cell Growth on TiO2Nanotubular and Flat Substrates
Keywords: TiO2 nanotube layers; Ti sheets; atomic layer deposition; coatings; cell growth; TiO2 nanotube layers; Ti sheets; atomic layer deposition; coatings; cell growth